2000
DOI: 10.1001/archinte.160.18.2717
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Medical Injuries in Older Patients

Abstract: Injuries associated with hospitalization are more common in older (>/=65 years) than in younger patients (<65 years), and they may be more severe and more often preventable. The increasing age of the population magnifies the importance of this problem. In this review, we first consider medical injuries in general and then review the literature for 6 categories: adverse drug events, falls, nosocomial infections, pressure sores, delirium, and surgical and perioperative complications. For each of these categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
2
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(171 citation statements)
references
References 147 publications
3
153
2
13
Order By: Relevance
“…[1,2] AEs are common across age groups, though the predominant drug class causing the AE in a particular age group may vary. Several studies have shown that the incidence of AEs is higher in elderly [3][4][5] and is associated with several factors, one of which is polypharmacy. A study in 1997 found that 35% of ambulatory older adults experienced an AE, and 29% required health care services (physician, emergency department visit or hospitalization) for the same.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] AEs are common across age groups, though the predominant drug class causing the AE in a particular age group may vary. Several studies have shown that the incidence of AEs is higher in elderly [3][4][5] and is associated with several factors, one of which is polypharmacy. A study in 1997 found that 35% of ambulatory older adults experienced an AE, and 29% required health care services (physician, emergency department visit or hospitalization) for the same.…”
Section: Introductionmentioning
confidence: 99%
“…60 For example, physiological reserves have been proposed as an alternative hypothesis to age per se. [60][61][62] Work undertaken to date has been dependent on hospital administrative data sets to generate variables to test in regression models with varying outcomes. 35,63 Elective admission and length of hospital stay was independently statistically associated with experiencing an AE in phase 1 of the study.…”
Section: Identification Of Patient-level Factors Predisposing Individmentioning
confidence: 99%
“…[55][56][57] In the Harvard Medical Practice Study, a retrospective study of adverse events in 30,000 patients, those age 65 and over accounted for 27% of the hospitalized population but 43% of the adverse events. In this study, four types of adverse events occurred at least twice as often in older patients: fractures, falls, nontechnical postoperative complications, and adverse events related to noninvasive treatments.…”
Section: Frail Elderly Patients Are At High Risk For Iatrogenic Complmentioning
confidence: 99%